The Ante-Nicene fathers: translations of the writings of the fathers down to A.D. 325 - Roberts, Alexander; Donaldson, James; Coxe, A. Cleveland; Menzies, Allan; Richardson, Ernest Cushing; Pick, Bernhard (Ante-Nicene Christian library., 1911)
v. 1. The apostolic fathers, Justin Martyr, Irenaeus -- v. 2. Fathers of the second century: Hermas, Tatian, Athenagoras, Theophilus, and Clement of Alexandria (entire) -- v. 3. Latin Christianity: its founder, Tertullian. I. Apologetic; II. Anti-Marcion; III. Ethical -- v. 4. Tertullian, pt. 4th; Minucius Felix; Commodian; Origen, pts. 1st and 2d. -- v. 5. Hippolytus, Cyprian, Caius, Novatian, Appendix -- v. 6. Gregory Thaumaturgus, Dionysius the Great, Julius Africanus, Anatolius and minor writers, Methodius, Arnobius -- v. 7. Lactantius, Venantius, Asterius, Victorinus, Dionysius, Apostolic teaching and constitutions, Homily, and Liturgies -- v. 8. The twelve patriarchs, Excerpts and epistles, The Clementina, Apocrypha, Decretals, Memoirs of Edessa and Syriac documents, Remains of the first ages.